Léxico y sintaxis en los diccionarios monolingües del español - María Antonia Martínez Linares; Dolores Azorín Fernández (Estudios de Lingüística, 1994)
In this paper we have tried to determine if monolingual Spanish Dictionaries take into account the relationship between Lexis and Syntax as one basis of their approach. We have also tried to establish whether failure to take this relationship into account, in a systematic way, may be a serious obstacle to the achievement of the aims of the Dictionary in question.